(untitled) (Italian Review of Legal History, 2024)
The essay explores the ways through which the trials held by the Special Court for the Defense of the State were publicized in newspapers through the study of a case: a trial for double murder held in Ravenna in April 1930. The Donati case has some peculiarities: it was a common crime, drawn into the jurisdiction of the Special Court through the application of Article 4 of Law 2008/26, which prohibited membership in dissolved parties, and the trial was held in the place where the crime was committed. The idea that the Author would like to verify, through an expansion of the research to other cases handled by the Special Court, is that this Court, as a pillar of fascism’s constitutional architecture, acted not only as a judicial Court but also as a cog in fascism’s propaganda machine, and that the press used the cases handled by the Special Court to create a ‘narrative’ that conveyed the myths necessary to build the national community.